Membangun Generasi Berkualitas Melalui Pendidikan Kesadaran Dan Kepatuhan Hukum - Irawan, Hendri (Universitas Tabanan, 2023)
The Importance of Education as a strategy to shape a quality generation through the enhancement of awareness and legal compliance to create a safe and prosperous society. The main focus of this research is to explore qualitative descriptive education methods as an effective analytical tool in understanding and describing the role of education in shaping individuals who are morally and legally responsible. The method used in this writing is a qualitative descriptive approach through a review of literature sources such as journals and relevant articles. Research findings indicate that the integration of awareness and legal compliance in education can have a positive impact on the moral attitudes and behavior of participants. The crucial role of educators in creating a supportive learning environment that inspires the development of character is also a major highlight in this article. The article details the importance of education in awareness and legal compliance, the Model of Education in Awareness and Legal Compliance, and the goals and implementation of legal awareness education. This article serves as a guide for education practitioners, policymakers, and researchers to better understand effective ways to shape a quality generation through holistic and sustainable educational efforts